Assessing Grammar By Using Communicative Activities To Employ Studentsâ Skill And Ability To Use English - *, Rukminingsih (Proceeding of International Conference on Teacher Training and Education, 2016)
Employing communication activities for teaching grammar canÂ  be a useful skill to learn and offer variety to the students and cater to the needs of learners who are keen to develop their ability to use English. It can be turned into a useful and even enjoyable enough experience, if real life tasks, student problemsÂ  and teacher requirements are taken into consideration and brought into balance in assessing grammar. To develop authentic assessment grammar activities, begin with the types of tasks that students actually need to do using the language. Grammar Assessment can then take the form of communicative drills and communicative activities used in the teaching process. It is related to scoring form andÂ  grammar ssessmernt and also how language teachers need to adapt their scoring proceduresÂ  to reflect the two dimenssion of both declarative knowledge and procedural knowledge . The qualitative case study reported in this paper explored theÂ  assessing grammar skills and ability in declarative and procedural knowledge regarding asÂ  communicative approach in grammar class. semi âstructure interviewsÂ  and Questioners Â are used to collect the main source data.Â  The results showed that the students felt their grammar class more challenging by having some types of tasks measuring the studentsâ grammar skill and ability. It built up their curiosity , interest and motivation in learning grammar.Â